Sepiolite/PVDF nanocomposite films for Ionic polymer metal composites actuators - Koh, Faith Jun Ning (Nanyang Technological University, 2020)
The fast bending response and low actuation voltage of ion-exchange polymer composite (IPMC) has allowed them to excel in applications such as actuators and sensors. Nafion is an example of an IPMC benchmark standard that is widely used; however, several inherent drawbacks of Nafion such as high cost and fixed physical properties have encouraged the search for new alternatives. In this report, we aim to tackle this issue through the fabrication of a novel poly-electrolyte film through modification of pristine Sepiolite (SEP) into the matrix of Poly(vinylidene) Fluoride (PVDF), a promising alternative to the commonly used Nafion. The modification of SEP is carried out using ionic liquid and Li+, which helps to increase the compatibility of the SEP with the PVDF matrix. Upon the addition of modified SEP into the PVDF matrix, inner microchannels are formed which act as hydrophilic pathways to facilitate higher mobility of ions within the film. Furthermore, substitution of exchangeable cations such as Mg2+ and Ca2+ in SEP with Li+ enhances the flow of ion migration due to the usage of a smaller ion, leading to an increase in overall ionic conductivity.